Sharp genetic discontinuity across a unimodal Heliconius hybrid zone (2012)
Hybrid zones are powerful natural systems to study evolutionary processes to gain an understanding of adaptation and speciation. In the Cauca Valley (Colombia), two butterfly races, Heliconius cydno cydnides and Heliconius cydno weymeri, meet and hybridize. We characterized this hybrid zone using a combination of mitochondrial DNA (mtDNA) sequences, amplified fragment length polymorphisms (AFLPs), microsatellites and sequences for nuclear loci within and outside of the genomic regions that cause differences in wing colour pattern. The hybrid zone is largely composed of individuals of mixed ancestry. However, there is strong genetic discontinuity between the hybridizing races in mtDNA and, to a lesser extent, in all nuclear markers surveyed. The mtDNA clustering of H. c. cydnides with the H. cydno race from the Magdalena Valley and H. c. weymeri with the H. cydno race from the pacific coast suggests that H. c. cydnides colonized the Cauca Valley from the north, whereas H. c. weymeri did so by crossing the Andes in the southern part, implying a secondary contact origin. Colonization of the valley by H. cydno was accompanied by mimicry shift. Strong ecological isolation, driven by locally adaptive differences in mimetic wing patterns, is playing an important role in maintaining the hybrid zone. However, selection on wing pattern alone is not sufficient to explain the genetic discontinuity observed. There is evidence for differences in male mating preference, but the contribution of additional barriers needs further investigation. Overall, our results support the idea that speciation is a cumulative process, where the combination of multiple isolation barriers, combined with major phenotypic differences, facilitates population divergence in face of gene flow. See also the Perspective by Mallet and Dasmahapatra © 2012 Blackwell Publishing Ltd.